African American students' experiences at "Urban Community College" - Dastmozd, Rassoul, author; Harbour, Clifford P., advisor (Colorado State University. Libraries, 2007)
This qualitative study investigated the holistic experiences of nine African American students at a predominately White two year comprehensive community college in the Midwest region of the U.S., "Urban Community College (UCC)." Each participant was interviewed twice; a 90-minute semi-structured face-to-face interview followed by a 45-minute follow up interview. The researcher used a phenomenological research method similar to but not the same as Moustakas's (1994) data reduction procedures to analyze the data (Willig, 2001). The analytical process for this study followed the traditional steps of doing a participant within case analysis followed by cross case analysis. The key findings of this study were presented using four salient domains from an inductive data analysis. The expectations and motivations domain described reason(s) that participants identified for attending UCC. The attributes domain explained talents/skills (assets) or enabling qualities or positive influencers and deficits or negative influencers that participants identified as they interfaced with the UCC college community. The interactions and rapport domains described participants' interactions and transactions with the academic and non-academic conditions at UCC. The term rapport defined participants' relationship(s) with the academic and non-academic conditions at UCC. The transformation and self-discovery domain explained how attending UCC or participating in this study changed the participants' lives and the new perspective(s) that they may have gained. The dynamic interplay among four salient domains revealed the essence of participants' shared experiences. The essence of participants' shared experience(s) is their desire for becoming contributing and functioning members of their communities and achieving social stability. The findings were analyzed, interpreted, and presented in relationship to the literature. The participants' experiences and their stories will serve as a beacon for the future African American students enrolling in a two year comprehensive PWI community college. The participants' experiences will not only add to research literature, but their experiences can also provide a two year comprehensive PWI community college learning opportunities about cultural competence and to devise policies, programs, and initiatives that can promote positive experiences for other African American students as well as other minority students as these students pursue their educational journey at these institutions.
Keywords: African-American; community college; predominantly white; urban education; community colleges; African Americans; educational sociology